Patient selection, pacing indications, and subsequent outcomes with de novo leadless single-chamber VVI pacing. Issue 11 (5th September 2019) - Piccini, Jonathan P; Stromberg, Kurt; Jackson, Kevin P; Kowal, Robert C; Duray, Gabor Z; El-Chami, Mikhael F; Crossley, George H; Hummel, John D; Narasimhan, Calambur; Omar, Razali; Ritter, Philippe; Roberts, Paul R; et al.
Abstract: Aims: Patient selection is a key component of securing optimal patient outcomes with leadless pacing. We sought to describe and compare patient characteristics and outcomes of Micra patients with and without a primary pacing indication associated with atrial fibrillation (AF) in the Micra IDE trial. Methods and results: The primary outcome (risk of cardiac failure, pacemaker syndrome, or syncope related to the Micra system or procedure) was compared between successfully implanted patients from the Micra IDE trial with a primary pacing indication associated with AF or history of AF (AF group) and those without (non-AF group). Among 720 patients successfully implanted with Micra, 228 (31.7%) were in the non-AF group. Reasons for selecting VVI pacing in non-AF patients included an expectation for infrequent pacing (66.2%) and advanced age (27.2%). More patients in the non-AF group had a condition that precluded the use of a transvenous pacemaker (9.6% vs. 4.7%, P  = 0.013). Atrial fibrillation patients programmed to VVI received significantly more ventricular pacing compared to non-AF patients (median 67.8% vs. 12.6%; P  < 0.001). The overall occurrence of the composite outcome at 24 months was 1.8% with no difference between the AF and non-AF groups (hazard ratio 1.36, 95% confidence interval 0.45–4.2; P  = 0.59). Conclusion: Nearly one-third of patients selected to receive Micra VVI therapy were for indications not associated with AF. Non-AF VVI patients required less frequent pacing compared to patients with AF. Risks associated with VVI therapy were low and did not differ in those with and without AF.